2017
DOI: 10.1136/heartjnl-2016-311027
|View full text |Cite
|
Sign up to set email alerts
|

Genomic basis of atrial fibrillation

Abstract: Atrial fibrillation (AF) is a prevalent arrhythmia associated with substantial morbidity, mortality and costs. Available management strategies generally have limited efficacy and are associated with potential adverse effects. In part, the limited efficacy of approaches to managing AF reflect an incomplete understanding of the biological mechanisms underlying the arrhythmia, and only a partial understanding of how best to individualise management. Over the last several decades, a greater understanding of genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 49 publications
1
29
0
5
Order By: Relevance
“…Interestingly, all of the causative genes of early repolarization syndrome have also been associated with atrial fibrillation. 24,25 There may be a common genetic background for atrial fibrillation and ventricular fibrillation related to early repolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all of the causative genes of early repolarization syndrome have also been associated with atrial fibrillation. 24,25 There may be a common genetic background for atrial fibrillation and ventricular fibrillation related to early repolarization.…”
Section: Discussionmentioning
confidence: 99%
“…VTE and AF are both blood-related polygenic conditions and are not fully understood genetically (Bapat, Anderson, Ellinor, & Lubitz, 2018; Hotoleanu, 2017). They share genetic risk factors and patho-physiological bases for clot formation (Shariff et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The deletion/insertion of a 287-bp intronic DNA segment resulting in double-deletion or insertion/deletion genotypes of the angiotensin-converting enzyme gene has been associated with failure of antiarrhythmic drug therapy in AF (Darbar et al, 2007). GWAS studies have identified more than 30 genetic loci in association with AF, suggesting previously unrecognized potential mechanisms of the disease (Bapat et al, 2018). For example, a recent GWAS study identified a novel AF locus comprising intronic and several highly correlated missense variants situated in the I-, A-, and M-bands of titin, which is the largest protein in humans and responsible for the passive elasticity of heart and skeletal muscle (Nielsen et al, 2018).…”
Section: Genetics Of Atrial Fibrillationmentioning
confidence: 99%